PENGARUH PELATIHAN PENINGKATAN KEMAMPUAN LITERASI DIGITAL IBU RUMAH TANGGA TERHADAP PENCEGAHAN PENIPUAN ONLINE DI KELURAHAN BUNGA TANJUNG KOTA TANJUNG BALAI - Dhea Astri Arifina Napitupulu; Sani Susanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of digital literacy training on the prevention of online fraud among housewives aged over 50 years in Bunga Tanjung Village, Tanjung Balai City. The increase in cases of digital fraud among the elderly highlights the importance of digital literacy as a preventive measure so that the community can use technology safely. This study uses a quantitative approach with a quasi-experimental method through a one-group pretest-posttest design. The research subjects consisted of 30 housewives, with an instrument in the form of a 25-item questionnaire that had been tested for validity and reliability. Data analysis included prerequisite tests (normality and linearity), variable tendency tests, and simple linear regression tests to see the influence between variables. The results showed that the participants' digital literacy skills were in the high category after participating in the training, as indicated by a significant increase in posttest scores compared to pretest scores. Online fraud prevention also increased significantly, and there was a positive and significant effect between digital literacy training and online fraud prevention, with a significance value of 0.000 < 0.05 and tcount > ttable (8.384 > 2.084). These findings prove that digital literacy training is effective in increasing the awareness and ability of housewives to recognize and avoid digital fraud. Similar training programs are recommended to be carried out continuously so that the digital resilience of the community becomes stronger.